Dissolution capacity and rheology of cellulose in ionic liquids composed of imidazolium cation and phosphate anions. (12th April 2019) - Zheng, Bingqian; Harris, Chaudhary; Bhatia, Surita R.; Thomas, Marie F.
Abstract : Cellulose is one of the most abundant natural polymer sources, but the applications of cellulose are limited due to difficulty in dissolving cellulose in water and common chemical solvents. In the past decades, ionic liquids have been studied to dissolve cellulose efficiently, sustainably, and in an eco‐friendly manner. In this study, a series of imidazolium‐based ionic liquids were synthesized to explore as solvents for cellulose, including 1, 3‐dimethylimidazolium dimethylphosphate ([mmim]dmp), 1‐ethyl‐3‐methylimidazolium dimethylphosphate ([emim]dmp), 1‐butyl‐3‐methylimidazolium dimethylphosphate ([bmim]dmp), 1‐hexyl‐3‐methylimidazolium dimethylphosphate ([hmim]dmp), 1‐ethyl‐3‐methylimidazolium diethylphosphate ([emim]dep), 1, 3‐diethylimidazolium diethylphosphate ([eeim]dep), and 1‐butyl‐3‐ethylimidazolium diethylphosphate ([beim]dep). Rheology experiments were conducted to study the flow behavior of cellulose in these ionic liquids and cosolvents. We found that the dissolution capacity of cellulose increases with decreasing viscosity of the solvent and that the rheological properties depend most strongly on the concentration of cellulose dissolved. Systems composed of cellulose in [mmim]dmp, [emim]dmp, and [emim]dep behave as viscoelastic gels, while formulations of cellulose in [bmim]dmp, [hmim]dmp, [eeim]dep, and [beim]dep show viscoelastic liquid behavior. These results will impact development of new solvents for processing of cellulose‐based polymeric materials.